Oculomotor Nerve Paralysis in a Patient with Thrombocytopenic Purpura and Antiphospholipid Syndrome - Rivera Rojas, Neiby Johana; Muñoz Martínez, Karen Marcela; Nassar Tobón, Andrea Catalina (MEDICA REVIEW. International Medical Humanities Review / Revista Internacional de Humanidades Médicas, 2022)
We describe the case of a patient with idiopathic thrombocytopenic purpura refractory to treatment, who was admitted due to headache, exotropia of the right eye, palpebral ptosis, severe thrombocytopenia, requiring transfusion. A contrasted brain MRI was performed which revealed subarachnoid hemorrhage in the right frontal operculum, requiring a negative infectious, deficiency, autoimmunity and vasculitic profile, with a profile for positive antiphospholipid syndrome. Vasa nervorum thrombosis was considered a possible pathophysiological mechanism, which favored incomplete oculomotor cranial nerve palsy. Anticoagulation with warfarin was started, immunomodulatory therapy was adjusted for the underlying disease, with favorable evolution on the part of the patient.